A review of the Toronto Zoo's head-starting program for recovery of the Blanding's turtle in Rouge Valley National Urban Park - Crilling, Keegan (My University, 2024)
Conservation reintroduction programs are valuable tools in supporting endangered or extinct species in the wild. With the many ways humans are causing adverse environmental impacts, it is crucial that we put effort into reversing our adverse effects to avoid large-scale irreversible changes to ecosystems. Places like zoos and sanctuaries already have facilities and staff extensively trained in caring for animals. These locations can be the key institutions to support various wildlife conservation projects. The Blanding’s turtle head-starting program at the Toronto Zoo and the turtle reintroduction into Rouge Valley National Urban Park are successful steps in restoring a population of an endangered species. The year that the individuals were released over the period 2014-2020 did impact the turtles’ chances of survival, with particularly low survival in 2020, but there was equal success with male and female releases and variable but equal success with hard and soft releases.